2020
DOI: 10.1111/puar.13251
|View full text |Cite
|
Sign up to set email alerts
|

Social Equity and COVID‐19: The Case of African Americans

Abstract: Emerging statistics demonstrate that COVID‐19 disproportionately affects African Americans. The effects of COVID‐19 for this population are inextricably linked to areas of systemic oppression and disenfranchisement, which are exacerbated by COVID‐19: (1) health care inequality; (2) segregation, overall health, and food insecurity; (3) underrepresentation in government and the medical profession; and (4) inequalities in participatory democracy and public engagement. Following a discussion of these issues, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(100 citation statements)
references
References 81 publications
3
97
0
Order By: Relevance
“…Outcomes associated with the daily conditions of Black life in the most vulnerable communities predispose Black people to a host of disparities, health and otherwise (Budoff et al. 2006; Gupta, Carrión‐Carire, and Weiss 2006; Hoberman 2012; Mehta et al 2006; Wright and Merritt 2020). COVID‐19, for some, further exposes and reiterates, for others, half a millennium of structural racism and repression targeted with administrative precision on the Black body.…”
mentioning
confidence: 99%
“…Outcomes associated with the daily conditions of Black life in the most vulnerable communities predispose Black people to a host of disparities, health and otherwise (Budoff et al. 2006; Gupta, Carrión‐Carire, and Weiss 2006; Hoberman 2012; Mehta et al 2006; Wright and Merritt 2020). COVID‐19, for some, further exposes and reiterates, for others, half a millennium of structural racism and repression targeted with administrative precision on the Black body.…”
mentioning
confidence: 99%
“…Research has found that Black residents living in segregated areas tend to have less equitable health outcomes, limited healthy food options, and increased mortality rates. Further, white residents tend to receive better health care access and processes than do Black residents (Wright & Merritt, 2020). Thus, where and with whom we live impact how long we live, and where and with whom we live are strongly influenced by structural racism, as cases like Flint, Michigan powerfully demonstrate (Nickels, 2019).…”
Section: Institutional Racism At a Glance: Segregation And Healthmentioning
confidence: 99%
“…Many factors explain these disparities, from these populations more likely to work in jobs putting them in contact with the virus, less able to socially distance, less access to clean water needed for handwashing, less access to equitable, high-quality healthcare, and more. More directly, racism and white supremacy in structures, institutions, and systems influence and, indeed, create these dynamics (Wright & Merritt, 2020).…”
Section: Where We Are Nowmentioning
confidence: 99%